Estruturas, arquitetura e evolucao do Complexo Granitoide Itaqui (SP) - Wernick, E.; Ferreira, C. J. (My University, 1993)
The Itaqui Granitoid Complex is a drop shaped WNW-ESE trending intrusion with its head' at west. Its contacts with the low-grade metamorphic rocks of the Sao Roque Group are intrusive at west, northwest, north and northeast, and tectonic at south and northeast. The complex is built up by four main intrusive phases which characterize a rising and unroofing process. Petrographically the Itaqui granite comprises five distinct magmatic associations in nine igneous units. -from English summary
Structures, architecture and evolution of the Itaqui Granitoid Complex
Keywords: deformation; granite; pluton emplacement; Brazil, Sao Paulo, Itaqui Complex